General recommendations for the management of breast cancer (St. Gallen Expert Consensus developed at the 16th th International Breast Cancer Conference) - V. F. Semiglazov; R. M. Paltuev; V. V. Semiglazov (Опухоли женской репродуктивной системы, 2020)
This article summarizes the results of the 16th St. Gallen International Breast Cancer Conference (March 2019), which traditionally resulted in the development of a new guideline for local/regional and systemic treatment of breast cancer.